The Allergen-Specific IgE Concentration Is Important for Optimal Histamine Release From Passively Sensitized Basophils - Stoffersen, Peter; Skov, Per S.; Poulsen, Lars K.; Jensen, Bettina M. (Frontiers in Allergy, 2022)
Background The basophil histamine release (HR) assay can be used for allergy diagnosis in addition to the conventional measurement of allergen specific IgE (sIgE). Passive sensitization of basophils increases the versatility and allows testing biological relevance of allergen-induced IgE cross-linking in any serum unbiased by the cellular component. However, not all patient sera perform equally well, and we hypothesized that the absolute level and fraction of sIgE affect the performance. Choosing birch pollen allergy as a model, we investigated the concentration of sIgE needed for successful passive sensitization using soluble or matrix fixed Bet v 1. Methods Twenty-eight sera with Bet v 1 sIgE (7 sera within each allergy class (1: 0.1-0.70 kUA/L, 2: 0.71-3.50 kUA/L, 3: 3.51-17.50 kUA/L, 4+: >17.50 kUA/L)) and a negative control serum pool were used to passively sensitize donor basophils, obtained from buffy coat blood (n = 3). The cells were incubated (30 min) with soluble allergen (rBet v 1 from 0.2 to 50 ng/mL), matrix fixed allergen (ImmunoCAPTM containing recombinant Bet v 1) or PMA/ionomycin mixture (maximal HR) and released histamine was quantified fluorometrically. Results The lowest level of Bet v 1 sIgE generating a detectable HR (HR > 10 % of maximal release) in all 3 runs was found to be 1.25 kUA/L (corresponding to allergy class 2, 0.71 – 3.50 kU/L). Furthermore, sera from allergy class 3 and 4+ ascertained a significant reproducible HR: 42/42 vs. 5/21 in allergy class 1 and 15/21 in allergy class 2. Using ImmunoCAPTMs containing Bet v 1 as a matrix-fixed allergen system similar results were obtained where the lowest sIgE concentration mediating a HR was 1.68 kU/L, and 7/7 for both allergy class 3 and 4+. Conclusion The results demonstrate that the IgE titer is strikingly robust in predicting the ability to sensitize basophils and produce a measurable HR.